2023
DOI: 10.2147/dmso.s399275
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Anthropometric Indicators and Cut Points for Predicting Metabolic Syndrome in Chinese Patients with Type 2 Diabetes Mellitus by Gender

Abstract: Purpose The best predictors and cut points for metabolic syndrome (MetS) in Chinese patients with type 2 diabetes (T2DM) were determined by comparing six anthropometric measures: body mass index (BMI), triglyceride-glucose (TyG), the product of TyG and waist-to-hip ratio (TyG-WHpR), the product of TyG and waist-to-height ratio (TyG-WHtR), the product of TyG and waist circumference (TyG-WC), and the product of TyG and body mass index (TyG-BMI). Patients and Methods Sixte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Mao et al conducted a study aiming to identify the optimal predictors and cut-off points for Metabolic Syndrome (MetS) among Chinese adults with Type 2 Diabetes Mellitus (T2DM). Their findings indicated that TyG-WC was the most effective predictor of MetS among women, while BMI emerged as the best predictor for both genders combined 35 . In contrast, our study revealed that TyG-WC was the superior predictor of MetS for both women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al conducted a study aiming to identify the optimal predictors and cut-off points for Metabolic Syndrome (MetS) among Chinese adults with Type 2 Diabetes Mellitus (T2DM). Their findings indicated that TyG-WC was the most effective predictor of MetS among women, while BMI emerged as the best predictor for both genders combined 35 . In contrast, our study revealed that TyG-WC was the superior predictor of MetS for both women and men.…”
Section: Discussionmentioning
confidence: 99%